The power of product: how food advertising affects children’s perceptions of child and non-child targeted food advertising? - Soares Guimaraes, Julia; Pritchard, Meghan; Sabir, Soulene; Vanderlee, Lana; Ramsay, Timothy; Elliott, Charlene; Potvin Kent, Monique (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Food advertising shapes children’s preferences for unhealthy foods, contributing to poor diets and increased risk of obesity and non communicable diseases. This study explored children’s perceptions of child and non-child-targeted food advertising. Methods Open-ended online interviews with 17 participants, recruited through convenience sampling, were conducted where children were prompted with four advertisements (ads): a child-targeted and non-child-targeted ad for both healthy (plain milk) and unhealthy (chocolate) foods. A thematic analysis was conducted. Results Most children expressed positive perceptions of the ads, and the reasons children described liking the ads included: (i) people in the ad eating the product, (ii) positive emotional appeal, (iii) pre-existing affinity with the product, and (iv) visibility of the product. However, most children expressed “negative purchase intent” to all ads due to a pre-existing aversion to the product. Many children who expressed pre-existing affinity with the product still expressed negative purchase intent because they preferred other brands or flavours of the product. Most children considered the type of product over the marketing techniques when asked about perceived targeted audience. The main themes found were: (i) product for everyone, and (ii) product for people that like the product. Conclusions Children’s perceptions, purchase intent and perceived targeted audience did not change between child-targeted and non-child-targeted ads. This study underscores the critical role of the product itself in influencing children’s responses to ads. It highlights the need for public policies and advertising regulations to focus on restricting promotions of unhealthy products rather than solely addressing marketing techniques or target audiences.